Side view thrombosis microfluidic device with controllable wall shear rate and transthrombus pressure gradient - Muthard, Ryan W. (2013)
Hemodynamic conditions vary throughout the vasculature, creating diverse environments in which platelets must respond. To stop bleeding, a growing platelet deposit must be assembled in the presence of fluid wall shear stress (τ(w)) and transthrombus pressure gradient (ΔP) that drives bleeding. We designed a microfluidic device capable of pulsing a fluorescent solute through a developing thrombus forming on collagen ± tissue factor (TF), while independently controlling ΔP and τ(w). Computer control allowed step changes in ΔP with a rapid response time of 0.26 mm Hg/s at either venous (5.2 dynes/cm(2)) or arterial (33.9 dynes/cm(2)) wall shear stress. Side view visualization of thrombosis with transthrombus permeation allowed for quantification of clot structure, height, and composition at various ΔP. Clot height was reduced 20% on collagen/TF and 28% on collagen alone when ΔP was increased from 20.8 to 23.4 mm Hg at constant arterial shear stress. When visualized with a platelet-targeting thrombin sensor, intrathrombus thrombin levels decreased by 62% as ΔP was increased from 0 to 23.4 mm Hg across the thrombus-collagen/TF barrier, consistent with convective removal of thrombogenic solutes due to pressure-driven permeation. Independent of ΔP, the platelet deposit on collagen had a permeability of 5.45 × 10(−14) cm(2), while the platelet/fibrin thrombus on collagen/TF had a permeability of 2.71 × 10(−14) cm(2) (comparable to that of an intact endothelium). This microfluidic design allows investigation of the coupled processes of platelet deposition and thrombin/fibrin generation in the presence of controlled transthrombus permeation and wall shear stress.